Educating Consultants for Multicultural Practice of Consultee-Centered Consultation. Issue 1 (2nd January 2017) - Ingraham, Colette L.
ABSTRACT: Literature about educating consultants with knowledge, skills, and dispositions to work effectively within culturally and linguistically diverse schools is scarce. Research suggests that additional attention is needed on the preparation of consultants to practice with multicultural competence. This article reviews theories and research and presents four educational strategies for preparing consultants for multicultural practice of consultee-centered consultation (CCC). Specific attention is given to ways that educators can teach and supervise learners of CCC by integrating issues of worldview, culture, and different perspectives, thereby scaffolding learning toward the development of multicultural competence in consultation.